How Does Salinity Shape Bacterial and Fungal Microbiomes of Alnus glutinosa Roots? - Thiem, Dominika; Gołębiewski, Marcin; Hulisz, Piotr; Piernik, Agnieszka; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2018)
Black alder (Alnus glutinosa Gaertn.) belongs to dual mycorrhizal trees, forming ectomycorrhizal (EM) and arbuscular (AM) root structures, as well as represents actinorrhizal plants that associate with nitrogen-fixing actinomycete Frankia sp. We hypothesized that the unique ternary structure of symbionts can influence community structure of other plant associated microorganisms (bacterial and fungal endophytes), particularly under seasonally changing salinity in A. glutinosa roots. In our study we analyzed black alder root bacterial and fungal microbiome present at two forest test sites (saline and non-saline) in two different seasons (spring and fall). The dominant type of root microsymbionts of alder were ectomycorrhizal fungi, whose distribution depended on site (salinity): Tomentella, Lactarius and Phialocephala were more abundant at the saline site. Mortierella and Naucoria (representatives of saprotrophs or endophytes) displayed the opposite tendency. Arbuscular mycorrhizal fungi belonged to Glomeromycota (orders Paraglomales and Glomales), however they represented less than 1% of all identified fungi. Bacterial community structure depended on test site but not on season. Sequences affiliated with Rhodanobacter, Granulicella and Sphingomonas dominated at the saline site, while Bradyrhizobium and Rhizobium were more abundant at the non-saline site. Moreover, genus Frankia was observed only at the saline site. In conclusion, bacterial and fungal community structure of alder root microsymbionts and endophytes depends on five soil chemical parameters: salinity, phosphorus, pH, SP as well as total organic carbon, and seasonality does not appear to be an important factor shaping microbial communities. Ectomycorrhizal fungi are the most abundant symbionts of mature alders growing in saline soils. However, specific distribution of nitrogen-fixing Frankia (forming root nodules) and association of arbuscular fungi at early stages of plant development should be taken into account in further studies.